Plasmon-assisted random lasing from a single-mode fiber tip - Khatri, Dipendra S. (Opt Express, 2020)
Random lasing occurs as the result of a coherent optical feedback from multiple scattering centers. Here, we demonstrate that plasmonic gold nanostars are efficient light scattering centers, exhibiting strong field enhancement at their nanotips, which assists a very narrow bandwidth and highly amplified coherent random lasing with a low lasing threshold. First, by embedding plasmonic gold nanostars in a rhodamine 6G dye gain medium, we observe a series of very narrow random lasing peaks with full-width at half-maximum ∼ 0.8 nm. In contrast, free rhodamine 6G dye molecules exhibit only a single amplified spontaneous emission peak with a broader linewidth of 6 nm. The lasing threshold for the dye with gold nanostars is two times lower than that for a free dye. Furthermore, by coating the tip of a single-mode optical fiber with gold nanostars, we demonstrate a collection of random lasing signal through the fiber that can be easily guided and analyzed. Time-resolved measurements show a significant increase in the emission rate above the lasing threshold, indicating a stimulated emission process. Our study provides a method for generating random lasing in the nanoscale with low threshold values that can be easily collected and guided, which promise a range of potential applications in remote sensing, information processing, and on-chip coherent light sources.